Respostas
respondido por:
58
Olá!!!
Resolução!!!
{ 2x + y = 0
{ 2x - y = 4
Método de substituição!!!
2x + y = 0
y = 0 - 2x
y = - 2x
2x - y = 4
2x - ( - 2x ) = 4
2x + 2x = 4
4x = 4
x = 4/4
x = 1
y = - 2x
y = - 2 • ( 1 )
y = - 2
O par ordenado é ( 1, - 2 )
Espero ter ajudado!!!
Resolução!!!
{ 2x + y = 0
{ 2x - y = 4
Método de substituição!!!
2x + y = 0
y = 0 - 2x
y = - 2x
2x - y = 4
2x - ( - 2x ) = 4
2x + 2x = 4
4x = 4
x = 4/4
x = 1
y = - 2x
y = - 2 • ( 1 )
y = - 2
O par ordenado é ( 1, - 2 )
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás